Effectiveness of The Power Of Two Learning Method in Achieving Maharatul Kalam (Study of Arabic Language Learning at the Faculty of Letters) - Nurjannah , Nurjannah (SEAN Institute, 2023)
Effective Arabic language learning requires good planning, including mastery of methods. The reality in the field, Arabic language learning still uses traditional methods, not varied, still monotonous. The power of two method in muhadatsah learning at the Faculty of Letters UMI is designed to foster a dynamic, more active relationship, educational interaction between lecturers and students, students and students with maharatul kalam to reveal various nuances of meaning in various oral texts 'al hiwaar' This study aims to determine the application and effectiveness of the use of the power of two learning method, describe the solution to the obstacles in its application in Arabic language learning at the Faculty of Letters UMI. Data collection methods with interviews, observation and documentation. Data processing methods with data reduction, data presentation and conclusion drawing. The results showed that Arabic language learning, the use of the power of two method gave benefits to learning strategies, communication skills and confidence in expressing their opinions. There is no best learning method, as stated by the lecturer, but learning together, practicing the ability to speak intensely and done together, is very effective with the power of two method, and solutions to the obstacles to the application of the power of two learning method in Arabic language learning at the Faculty of Letters UMI, namely: lecturers must be prepared with the material to be taught, analyzing student characteristics, time allocation, and monitoring the implementation of learning.